2021
DOI: 10.1016/j.heliyon.2021.e07536
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Moringa oleifera waste as a coagulant in goat soft cheese production

Abstract: Milk clotting enzyme (MCE) of Moringa oleifera from prepared seed cake (PSC) dissolved in acetate buffer pH 5.0 recorded the highest activity compared to other samples, as well as 20–40% saturation of ammonium sulfate precipitated MCE with 28.20% yield and 1.01 purification fold. The proteolytic activity (PA) of crude MCE from Moringa oleifera PSC was higher than those of partial purified MCE with 180.81 and 155.47 as MCA/PA ratio, respectively. PSC moringa MCE exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
0
1
Order By: Relevance
“…CA values in all treatments were lower than the results of the study by [22] showed that the CA value of the M. oleifera extract with the participation of 20-40% ammonium sulfate was 2.47 U/ml. This difference in results could be due to the different concentrations of ammonium sulfate used, the type of substrate used in our study, the CA test was carried out using sodium caseinate, while in the study of [22] the substrate used is azocasein. Figure 2 shows the optimum pH for the enzyme incubation of M. oleifera extract to hydrolyze casein at pH 6-7.…”
Section: Caseinolytic Activity Of M Oleifera Seeds Extracted By Fmase...contrasting
confidence: 69%
“…CA values in all treatments were lower than the results of the study by [22] showed that the CA value of the M. oleifera extract with the participation of 20-40% ammonium sulfate was 2.47 U/ml. This difference in results could be due to the different concentrations of ammonium sulfate used, the type of substrate used in our study, the CA test was carried out using sodium caseinate, while in the study of [22] the substrate used is azocasein. Figure 2 shows the optimum pH for the enzyme incubation of M. oleifera extract to hydrolyze casein at pH 6-7.…”
Section: Caseinolytic Activity Of M Oleifera Seeds Extracted By Fmase...contrasting
confidence: 69%
“…Table 1 shows that in the first stage of precipitating ammonium sulfate purification, MCA activity increased from RLP E. faecium 1.15 to 0.83 (23.51 U/mL), with a yield of 3.68 percent. When compared to Moringa oleifera purified by 1.01 folds using precipitation ammonium sulfate (40%) with milk clotting activity of 384 SU/ml [5]. Furthermore, the purification using Sephadex G-50 can increase the purity to 6.71 with a yield of 1.31%.…”
Section: Purification Of Rlp From E Faecium 115mentioning
confidence: 99%
“…Comparison of MCA and PA values is used as a reference to compare potential enzyme activity as an alternative to renin [8]. The purified enzymes from Moringa oleifera ratio MCA/PA of 155,47 [5]. The results of other studies reported that purified enzymes from Dregea sinensis had an MCA/PA ratio of 27.31 [19].…”
Section: Purification Of Rlp From E Faecium 115mentioning
confidence: 99%
“…According to Adetunji and Babalobi (2011), the use of plants extracts as coagulants in the production of soft cheese has been known for a long time. Previous research used coagulant ingredients derived from plants such as spinach leaf extract (El-Sayed, 2020), Moringa oleifera (Abdeen et al, 2021), Cynara L. (Roseiro et al, 2003), papaya latex (Malaka et al, 2017;Sulmiyati and Said, 2019), cassava powder (Dhuol and Hamid, 2013), sunflower seeds (Nasr et al, 2016), Calotropis procera latex (Akinloye and Adewumi, 2014;Ojedapo et al, 2014), and Calotropis gigantea latex (Margoutomo et al, 2019;Bulkaini et al, 2020;Witono et al, 2003). The present work's novelty lies in the sense that it focused on using biduri leaf extract obtained from the biduri plant (Calotropis gigantea).…”
Section: Introductionmentioning
confidence: 99%